2016
DOI: 10.1016/j.ccep.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Delayed Rectifier Potassium Channels in Health and Disease

Abstract: Cardiac delayed rectifier potassium channels conduct outward potassium currents during the plateau phase of action potentials and play pivotal roles in cardiac repolarization. These include IKs, IKr and the atrial specific IKur channels. In this chapter, we will review the molecular identities and biophysical properties of these channels. Mutations in the genes encoding delayed rectifiers lead to loss- or gain-of-function phenotypes, disrupt normal cardiac repolarization and result in various cardiac rhythm di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 182 publications
(179 reference statements)
0
37
0
1
Order By: Relevance
“…K V 7.1 consists of four α-subunits which co-assemble with KCNE1 β-subunits to generate the I Ks current. The KCNQ1 α-subunit has a voltage sensing domain (S1–4), a pore forming domain (S5–6), as well as intracellular N- and C-termini [8]. LQT1 manifests on the surface electrocardiogram as a broad-based and symmetrical T-wave with a prolonged QTc interval [9].…”
Section: Genetics Of Lqtsmentioning
confidence: 99%
See 1 more Smart Citation
“…K V 7.1 consists of four α-subunits which co-assemble with KCNE1 β-subunits to generate the I Ks current. The KCNQ1 α-subunit has a voltage sensing domain (S1–4), a pore forming domain (S5–6), as well as intracellular N- and C-termini [8]. LQT1 manifests on the surface electrocardiogram as a broad-based and symmetrical T-wave with a prolonged QTc interval [9].…”
Section: Genetics Of Lqtsmentioning
confidence: 99%
“…hERG (human Ether-à-go-go -Related Gene) or KCNH2 codes for the voltage-gated pore forming α-subunit of the inwardly rectifying potassium channel subunit K V 11.1. The KCNH2 α-subunits form a complex with KCNE2 , a single transmembrane protein homologous to KCNE1 , to generate the I Kr current, intimately involved in membrane repolarization [8]. Heterozygote KCNH2 mutations exert a dominant-negative effect on wild-type hERG channel-associated I Kr currents by impairing trafficking pathways or altered channel kinetics of the resulting co-assembled hERG heterotetramers [15].…”
Section: Genetics Of Lqtsmentioning
confidence: 99%
“…It was shown that PKA-mediated phosphorylation of KCNQ1 at serine 27 is critical for I Ks . Yotiao (AKAP9) effectively scaffolds PKA and protein phosphatase-1 (PP-1) to KCNQ1, maintaining its phosphorylation levels during upstream receptor activation [ 41 ]. The S1570L mutation was found in the KCNQ1-binding domain of yotiao, representing 2% of the clinically-robust LQTS-exhibiting patients.…”
Section: Polymorphisms/mutations In Akaps and Cvdsmentioning
confidence: 99%
“…Delayed rectified potassium channels are responsible for ventricular repolarization and stabilization of membrane potential. With disruption of the normal function of these channels and multiple potassium currents, electrical instability may result in malignant tachyarrhythmias [7].…”
Section: Discussionmentioning
confidence: 99%